Digital literacy and its effect on learners’ civic engagement in adult and vocational education in Nigeria - Bessong, Columbus Deku; Ewuru, Agnes Awoli; Bessong, Napoleon Osang; Omang, Theresa Nkim; Olori, Gloria Iniobong; Patrick, Elizabeth Odije; Olofu, Agbade Paul; Olori, Christian Nwachukwu (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Several works on the benefits of Information and Communication Technology (ICT) in society’s survival have been recognised by experts. However, in reality, the use of ICT in developing countries like Nigeria is still in its infancy due to their lack of knowledge about it. This study examines the effect of digital literacy on the civic engagement of learners in adult and vocational education in Nigeria. It adopted a non-equivalent control type of quasi-experimental research design involving the experimental and control groups. The sample size was 140 learners drawn from public adult and vocational education centers across Nigeria. The data-collecting instrument was the “Civic Engagement Test” (CET). Data were analysed using mean, standard deviation and analysis of covariance. Findings show that learners exposed to digital literacy had a higher positive effect on civic engagement than basic literacy. Furthermore, cooperative learning style adopted as a moderating variable had a higher civic engagement mean score than solitary. On interaction effect, the study concluded that basic literacy had a more positive effect than digital literacy, hence the need for the provision of necessary facilities to promote digital literacy skills among learners.